Close calls in obstetrics: lessons from maternal near miss cases at a tertiary hospital - Banumathy, M.; Preethikka (International Journal Of Community Medicine And Public Health, 2025)
Maternal near-miss (MNM) events offer critical insight into the gaps and successes in obstetric care without the finality of mortality. Evaluating these cases helps identify missed opportunities, systemic weaknesses, and areas for improvement in clinical response. This case series includes nine MNM cases. Four cases had hypertensive disorders five had haemorrhagic complications. Two women in hypertensive group had Antepartum eclampsia around 32 weeks, both required emergency cesarean sections and intensive care. They are also screen positive for Preeclampsia and on aspirin prophylaxis. Another patient developed eclampsia on postpartum day 10 revealing posterior reversible encephalopathy syndrome (PRES). Fourth patient, a twin gestation at 33 weeks, an IVF conception presented with breathlessness and was diagnosed with peripartum cardiomyopathy. Among the five with haemorrhage complications, two had massive placental abruption at 35 weeks. One with Takayasu arteritis and one with dilated cardiomyopathy had Postpartum haemorrhage (PPH), managed with B-Lynch sutures. Third one had atonic PPH and fourth patient had traumatic PPH which required uterine artery embolization. The final case had postoperative intramyometrial haemorrhage on 2nd postoperative day after cesarean myomectomy, requiring emergency laparotomy. All patients received Packed red blood cell [PRBC] transfusion and intense monitoring done. All nine patients recovered without severe morbidity and length of hospital stay being 5-7 days. Enhanced antenatal screening, postpartum vigilance, and robust emergency systems are essential to reduce maternal morbidity, Early detection and initiation of action through the 4 R’s: Readiness, Recognition, Response, and Reporting -is the mandate.